Biological effects of drilling fluid towards marine organisms - A. Azmi, Nurul Hidayah (2016)
Concern has grown in recent years on the impacts of operational discharges from petroleum exploration and production activities offshore towards marine organisms. When these substances discharge to the ocean, they may persist in the water column and seabed resulting in short-term and long-term effects to the marine environment. Oil based drilling fluid (OBDF) has shown to cause lethal effects and contribute to high mortality towards marine organisms compared to water based drilling fluid (WBDF) and synthetic based drilling fluid (SBDF). Drilling fluid and its components may induce histological alterations to the tissues and organs of marine life, which in turn lead to the death of organisms as a result of organ structural and functional impairment. Field studies on benthic communities demonstrated that the biological effects of OBDF were more severe compared to WBDF and SBDF which include changes in species diversity, abundance and alterations to community structure. The extend of OBDF effects was longer and occurred in the range of 500 to 1,000 m or even more. While WBDF and SBDF were minor and localized in the range of 50 to 250 m. The effects are mainly due to physical changes and natural processes irrespective of the type of drilling fluid. Biological effects due to petroleum-related activities are mostly seen if elevated oil concentration is present. As a conclusion, drilling fluid must be carefully designed and formulated to lessen the biological impact to marine life. WBDF and SBDF shall be used whenever possible but proper and less toxic chemicals need to be carefully chosen during formulation. OBDF shall be prohibited and replaced with a more environmentally acceptable SBDF to minimize the biological effects to marine life.